Organisational knowledge and the effects of 'billable' hours. (17th July 2006) - Garrick, John; Chan, Andrew
This paper examines organisational knowledge in terms of how people in workplaces understand and define it. Organisational knowledge has developed to a point where the nature of research and knowledge can no longer be tied to the confines of scientific knowledge. Instead, knowledge is increasingly classified in terms of its contribution to organisational effectiveness. Where alternative (non-scientific) means can better achieve organisational effectiveness, hard science may not be necessary. Knowledge, in this sense, has worth in its use value such as 'billable hours', 'measurable return' and its ability to achieve something outside of itself. In questioning the authority through which knowledge is legitimated in such firms, we revisit Lyotard's (1984, p.9) pertinent question: 'Who decides what knowledge is, and who knows what needs to be decided?' We draw onhis theory of performativity to examine the ways new organisational knowledge can be constructed.